Structure of situation motor stereotips of karate competitors and karate representatives - Ilievski, E. S.; Shala, E.; Kostovski, Z. (Sports Science and Health, 2018)
This survey was conducted on a deliberate sample of 32 respondents, 16 karate competitors and 16 karate representatives, male, from the Republic of Macedonia. The main goal of this research was to determine the structure of situational motor stereotypes (situational karate tests) between karate competitors and karate representatives in a sports fight for each category separately. In the study, a total of 15 variables of karate elements applied in a sports karate combat divided into 5 spaces were used: three variables of attack with one hand strike, three variables of attack with two hands techniques, three variables of attack with three hands techniques, three variables of attack with one stroke with leg and three variables of attack with combined techniques of hands and legs. The results of the factor analysis obtained by this study show the extraction of 3 significant latent dimensions in the category of competitors and 5 significant latent dimensions in the category of representatives.